REHIDRACIJA U SPORTU - Labud Janković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
During sport activities it is obviously that body loses liquid by sweating, and ensuing consequence is reduction of body weight. About 85-90% of body reduction is consisted of water. If sportsman have opportunities to consume special sport beverages during his exercises or trainings, he should use it in definite time periods, but not in large quantities. Hydration is a process occurring during and after training activities. To evaluate level of dehydration it is necessary to measure body weight before and after activities. From that it is easy to determine quantity of liquid( volume) necessary for hydration. Lost liquid during sport activities should be redeem as early as possible-not later than 1-2 hours. Except water, a body loses other substances, such as some quantities of electrolytes and carbon hydrates. There are various beverages for quick redemption an recovery. These are hydration-energetically beverages